Auto-confusion of Ephestia cautella (Walker) infesting dried fruits in a confectionery factory store. (December 2020) - Trematerra, Pasquale; Colacci, Marco
Abstract: We assessed the effectiveness of a pheromone auto-confusion method applied for a three-year study (Years 1–3) in a confectionery factory store infested by almond moths, Ephestia cautella (Walker), based on pheromone traps and the presence of spermatophores in females captured with water traps. The application of Exosect® SP Tab pheromone dispensers, at a rate of 1 tablet per 25 m 2 floor area, combined with water traps eliminated a great numbers of males and females and reduced mating and population levels of E. cautella . The results confirmed that when auto-confusion was applied (Years 2–3) the percentage of mated females was lower compared with the previous year (Year 1), which was used as the control. The auto-confusion provides continuous activity against E. cautella adults and is a good approach to Integrated Pest Management that reduces the need for chemical treatments. Highlights: Almond moth, Ephestia cautella, is one of main insect pests of stored dried fruits. Pheromone Auto-confusion, alternative to chemicals, was used against infestation of E. cautella . In an IPM context, auto-confusion by Exosex SP Tab was effective in the control of E. cautella . The use of auto-confusion controlled E. cautella and reduced chemical spray in store of dried fruits.